(untitled) (Practitioner Research, 2022)
The COVID-19 pandemic has changed the education system, impacting teachers in various ways. Apart from the difficulty in e-Learning modes of instruction and insufficient social support, teachers must keep instructional time and application use at high performance. Due to distancing learning also, Ujian Pencapaian Sekolah Rendah (UPSR) has been abolished. In responding to the current school-based assessment and the challenging factor of Malaysians’ educators to stay ahead in the digital post-COVID-19 age, we have invented a new learning environment using HyperDoc with Google Sites (GS). Hence, this study was set out to explore sample views on the pedagogical strategy regarding GS application and to elaborate further on the resulting development of students. A case study was conducted with two participating lecturers, and 22 students from a teacher training institute (IPGKDa) and data analysis was carried out manually using open and thematic coding methods. In particular, we have categorised the participants’ responses into two main themes: teachers’ dissatisfaction and impact on students’ learning. The results suggest that utilising digital technologies in meaningful ways would become the answer to bridge the gap despite the pandemic crisis. The authentic learning environment strategies have provided directions to accelerate a highly competent 21st-century learner. As the teacher trainee institution, we aim to reinvent a better future post-COVID-19 for sustainable education by implementing and curating technology solutions that will meet the needs of current educators, especially primary school teachers. Strategies employed would also be able to guide further research in Malaysia to cope with the educational loss and, simultaneously, prepare the independent students for a future post-COVID-19.